Perbandingan Pengaruh Motivasi Belanja Terhadap Customer Satisfaction Melalui Utilitarian Value Di Hypermarket Dan Pasar Tradisional Kota Surabaya - Ardelita, Fanny; Ardhanari, Margaretha; Supriharyanti, Elisabeth (Kajian Ilmiah Mahasiswa Manajemen, 2017)
This study aims to determine and analyze the comparison influence of spending motivation on customer satisfaction through utilitarian value in Hypermarket and Traditional Market of Surabaya City. This research is a type of quantitative research that uses the analysis of numbers and calculations using statistical methods. Sampling technique in this study using non probability sampling, the sample used as much as 100 respondents with 2 times the filling is adjusted with 2 objects as a comparison. Data were collected through questionnaires and then processed by multiple linear regression analysis using IBM SPSS Statistics 23 application. The results of this study indicate that Monetary Saving has no positive effect on Utilitarian Value in Hypermarket of Surabaya City, Monetary Saving has positive effect on Utilitarian Value in Surabaya Traditional Market, Convenience has positive effect on Utilitarian Value in Hypermarket Surabaya, Convenience has no positive effect on Utilitarian Value in Traditional Market of Surabaya City, Utilitarian Value has positive influence on Customer Satisfaction in Hypermarket and Traditional Market of Surabaya City, there is difference of Satisfaction to Consumer in Hypermarket and Traditional Market of Surabaya City.